(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The article describes some issues of the development of cotton cultivation in the Ferghana valley during the colonial period. Also, the process of buying cotton and transporting fiber to the metropolis by companies operating in Ferghana region was partially analyzed based on archive documents.